Spór o „niezrozumialstwo” w dwudziestoleciu międzywojennym - Panek, Sylwia (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2018)
This polemic was the product of Karol Irzykowski’s article Niezrozumialstwo [Dysunderstandableness] published in 1924. The curtain of literary discourse was first raised on the pages of the Warsaw weekly Wiadomości Literackie and later, to the end of the interbellum in various newspapers such as Przegląd Wieczorny, Zwrotnica, Goniec Krakowski, Gazeta Artystów, Przegląd Warszawski, Kurier Wileński and Pion. The polemic, over the rationale and function of dysunderstandable literature, engaged renowned writers and literary critics such as Jerzy Hulewicz, Jan Nepomucen Miller, Stanisław Ignacy Witkiewicz, Tadeusz Peiper, Julian Przyboś and Jan Brzękowski.
The Interbellum Polemic Over “Dysunderstandableness”
Keywords: Karol Irzykowski; Niezrozumialstwo; polemika krytycznoliteracka